Pengaruh Personal Selling Terhadap Keputusan Mahasiswa/I Dalam Memilih Kampus Politeknik LP3I Tasikmalaya - Lestari, Nurindah; Budiman, Arip; Ernawati (EKOBIMA, 2025)
This study aims to determine how much influence the Current Ratio (CR) has on profit growth at PT Surya Citra Media, Tbk. The variable in this study are Current Ratio (X) and profit growth (Y). The population includes all quarterly financial reports at PT Surya Citra Media and the sample of this studi is quarterly financial reports for the last five years 2018-2022. The techniques used are documentation and literature review. The data analysis techniques used in this study are Simple Regressions Analysis, Normality Test, Heteroscedasticity Test, and Autocracy Test. The result of the studi indicate that the Current Ratio (CR) has no effect on Profit Growth.